2023
DOI: 10.1021/jacs.3c02570
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Rh-O5/Ni(Fe) Site for Efficient Biomass Upgrading Coupled with H2 Production

Abstract: Designing efficient and durable bifunctional catalysts for 5-hydroxymethylfurfural (HMF) oxidation reaction (HMFOR) and hydrogen evolution reaction (HER) is desirable for the co-production of biomass-upgraded chemicals and sustainable hydrogen, which is limited by the competitive adsorption of hydroxyl species (OHads) and HMF molecules. Here, we report a class of Rh–O5/Ni­(Fe) atomic site on nanoporous mesh-type layered double hydroxides with atomic-scale cooperative adsorption centers for highly active and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(30 citation statements)
references
References 41 publications
1
29
0
Order By: Relevance
“…(b) Comparison of the cell voltages required to drive different current densities for HOR//HER electrolysis and OER//HER electrolysis. Reproduced from ref . Copyright 2022 American Chemical Society.…”
Section: Paired Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…(b) Comparison of the cell voltages required to drive different current densities for HOR//HER electrolysis and OER//HER electrolysis. Reproduced from ref . Copyright 2022 American Chemical Society.…”
Section: Paired Reactionsmentioning
confidence: 99%
“…LDHs can be modified as ideal dual-functional electrocatalysts, enabling the coupling of the HOR and the HER under alkaline conditions. Zeng et al . recently reported a “new” class of catalysts consisting of Rh-O 5 /Ni­(Fe) atomic sites incorporated into nanoporous mesh-type, layered double hydroxides, which reportedly exhibit the highest level among catalysts reported.…”
Section: Paired Reactionsmentioning
confidence: 99%
“…Electrochemical water splitting has been widely recognized as a promising approach to generate hydrogen with zero emissions. In general, water electrolysis can be operated in either acidic or alkaline media. In view of the fact that most oxygen-evolution catalysts at the anode are subjected to corrosion in acid, alkaline anion-exchange-membrane water electrolysis (AEMWE) is more competitive and widely applied in industry for scalable hydrogen production. ,, Despite intensive investigations in cost-effective alternative catalysts over the past several decades, the most efficient catalysts for the hydrogen evolution reaction (HER) in AEMWE are still based on Pt, inherently owing to its near-optimal hydrogen absorption energy. However, the conventional Pt/C catalysts are suffering from high cost, low HER mass activity (especially in alkaline media), , and insufficient stability, which pose big obstacles for the large-scale rollout of Pt catalysts in AEMWE. , …”
Section: Introductionmentioning
confidence: 99%
“…19 Additionally, the sluggish HER kinetics of NiFe-LDH can be accelerated by the same strategy. 20 Wang et al reported that the Cl-coordinated Pt single site decreased the energy barrier of water dissociation and optimized the H binding energy, accelerating the HER kinetics. 21 As a platinumgroup metal, iridium (Ir), especially the Ir single atoms, are believed to significantly improve the OER activity by regulating the adsorption of reaction intermediates.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For example, Zhang et al proposed that the interaction of Au single atoms and NiFe-LDH regulated the charge density of active Fe sites, which prompted the adsorption of hydroxide and decreased the energy barrier of the formation from *O to *OOH, thus enhancing the OER performance . Additionally, the sluggish HER kinetics of NiFe-LDH can be accelerated by the same strategy . Wang et al reported that the Cl-coordinated Pt single site decreased the energy barrier of water dissociation and optimized the H binding energy, accelerating the HER kinetics .…”
Section: Introductionmentioning
confidence: 99%